Numerical simulation and experimental research on optimization of pneumatic convey system in pneumatic seeder - Fang Guo; Kaiqi Liu; Genhao Liu; Senhao Wang; Zhanfeng Hou; Jiacheng Li; Yu Ma (PLoS ONE, 2025)
The use of pneumatic seeders for coated grass seed effectively addresses the challenge of seed establishment in arid and semi-arid regions, significantly contributing to the mitigation of soil desertification. However, during pneumatic seeder operations, high airflow velocities can lead to increased seed breakage rates, while low airflow velocities may result in blockages. To address these issues, this study employs both experimental and simulation methods to optimize the pneumatic conveying system of the seeder. A theoretical model of the pneumatic conveying system was developed to analyze the velocity field, pressure field, and seed trajectory within the flow field. The study focused on optimizing three parameters: Diameter of the throat outlet, diameter of the throat inlet, and the seed inlet angle. The key findings are as follows: (1) An optimized throat diameter of D 2 = 58 mm is less prone to blockage; (2) Optimization of the neck ratio does not effectively mitigate the blockage issue; and (3) A seed inlet angle of α = 77° reduces seed breakage. This research elucidates the mechanisms of airflow and seed distribution within the pneumatic conveying system, providing solutions to minimize seed breakage and blockage, thereby enhancing the design and broader application of pneumatic seeders.